Pengembangan Inovasi Produk Gula Merah di Desa Cipaku Kecamatan Mrebet Kabupaten Purbalingga - Santosa, Hendri Dian; Fauziyah, Eka Putri Hana Nur; Nuansari, Larasatri; Adawiyah, Wiwiek Rabiatul; Sudjadi, Achmad; Fahmi, M. Noor (Jurusan Ilmu Ekonomi dan Studi Pembangunan | Universitas Jenderal Soedirman, 2025)
Cipaku Village, located in Purbalingga, Central Java, is a center for traditional palm sugar production with significant yet untapped economic potential. This community service program aims to assist palm sugar farmers through rebranding and packaging innovation. Using a collaborative approach, the program includes market surveys, new packaging design, and e-commerce marketing strategies. The results indicate improvements in product quality and appeal, as well as the adoption of sustainable farming practices. However, challenges such as a lack of marketing knowledge and limited access to capital continue to hinder the farmers' business development. Therefore, ongoing collaboration is needed to sustain these innovations.